Applicability of kegel exercises in different urinary incontinences in women: Systematic review - Martins Pires, Luis Felipe; Ribeiro da Costa, Matheus André; Urzeda Vitória, Estela; Gontijo de Souza, Mariana; Luz Xavier, Larissa Rebeca; Oliveira, Rodrigo Franco de (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Introduction: Urinary incontinence (UI) is the involuntary loss of urine. The condition also happens when there are small daily leaks. Objective: The aim of this study was to conduct a systematic review that verified the efficacy of Kegel's exercise in UI in women. Methodology: This is a systematic review, in which searches were conducted for articles related to the theme "Kegel Exercise in Urinary Incontinence in Women" in the PubMed, LILACS and SCIELO databases, the search was carried out starting on March 1, 2023 and ending on June 1 of the same year and the selection of articles was for the last 5 years. The inclusion criteria were full-text articles that talked about UI in women and the applicability of Kegel's exercise in treatment and studies with intervention, exclusion criteria were articles from the proposed period and which did not corresponded with the inclusion criteria. Altogether, 191 articles were found, after removal of articles off the subject and repeated 7 studies remained to be evaluated on the PEDro scale, among them 6 were suitable for use in the study. Results: To evaluate the articles, the PEDro scale consists of 11 questions containing yes or no answers that help validate the quality of clinical trial studies, the scores of the articles evaluated and elected in this scale of the study was 70%, in all, 6 articles were analyzed by the PEDro scale. Conclusion: Finally, it is concluded that the use of kegel exercises for the treatment of UI in women is effective, and should also be used as a method of prevention for possible incontinences, thus strengthening the pelvic floor with the exercises.